We have the system
![\begin{gathered} y=x^2-20 \\ y=x-8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6qmh97jnfvnuxvones989lszgdbusligco.png)
So we can equalize the two equations to get x
![\begin{gathered} x^2-20=x-8 \\ x^2-20+8-x=0 \\ x^2-x-12=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/shh8xo4rncqgnt0k05spyyjs4cece3g1ra.png)
So now we can solve the quadratic equation to find x, we are going to use the quadratic formula
![(-b±√\left(b²-4ac\right))/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/tlueqm0j0dgli2iy86dbgthhsxkcixa0nb.png)
We have a = 1, b= - 1 and c = -12, so replacing we get
![(-(-1)±√\left((-1)²-4\cdot1\cdot(-12)\right))/(2\cdot(1))](https://img.qammunity.org/2023/formulas/mathematics/college/tal6pbsid34a828nii8pzydrvzvvg0fam0.png)
this is
![(1\pm√(1+48))/(2)=(1\pm√(49))/(2)=(1\pm7)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/vr8qbbb4fmvelwubqlum8rrlhjqwvj1iso.png)
Then the solutions for x are x = (1 - 7)/2 = -6/2 = -3, and x = (1+7)/2 = 8/2 = 4. Now we replace in the second equation and we get two solutions for y, using x = -3 we get y = -3 - 8 = -11, and using x = 4 we get y = 4 - 8 = -4. So the two points are: (-3,-11) and (4,-4). THE ANSWER IS D.